2014
DOI: 10.1515/ijcre-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

CFD-DEM Modeling of CO2 Capture using Alkali Metal-Based Sorbents in a Bubbling Fluidized Bed

Abstract: This paper describes a CFD-DEM modeling of CO 2 capture using K 2 CO 3 solid sorbents in a bubbling fluidized bed, which takes into heat transfer, hydrodynamics, and chemical reactions. Shrinking core model is applied in reaction kinetics. Simulation and experiment results of bed pressure drop and CO 2 concentration in the reactor exit agree well. Instantaneous dynamics as well as time-averaged profiles indicate detailed characteristics of gas flow, particle motion, and chemical reaction processes. The simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The results showed that CO 2 conversion mainly occurred in the early stage of the reaction, and with the increase of gas flow rate, the gasification time was greatly shortened. Zhang et al 27 developed a CFD‐DEM model for the capture of CO 2 by K 2 CO 3 solid adsorbent in a BFB. The study revealed that bubbles can promote mixing and enhance the reaction yet are detrimental to the short‐path gas reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that CO 2 conversion mainly occurred in the early stage of the reaction, and with the increase of gas flow rate, the gasification time was greatly shortened. Zhang et al 27 developed a CFD‐DEM model for the capture of CO 2 by K 2 CO 3 solid adsorbent in a BFB. The study revealed that bubbles can promote mixing and enhance the reaction yet are detrimental to the short‐path gas reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Shan et al [21] presented a coupled CFD-DEM analysis on the impact behaviour of a granular flow falling from an inclined slope into a water reservoir. Zhang et al [22] used a CFD-DEM modelling of CO 2 capture using K 2 CO 3 solid sorbents in a bubbling fluidized bed. The simulation results of the bed pressure drop and CO 2 concentration in the reactor exit agreed well with the experimental results, with the simulation results showing clear core-annular and strong back-mixing flow patterns.…”
Section: Introductionmentioning
confidence: 99%